DELINEATION OF NUTRIENT MANAGEMENT ZONES IN MAIZE TRACTS OF TELANGANA USING MAXIMUM CURVATURE METHOD - T. L. NEELIMA; D. SRINIVASA CHARY, V. B. PANDIT, T. ANJAIAH, M. UMA DEVI (The Journal of Research, PJTSAU, 2023)
To maximize financial gain, minimize environmental impact, and improve soil and crop management, soil fertility must be maintained uniformly. Delineation of management zones (MZs) is the one option to divide soil variability in to different soil fertility classes. MZs with uniform production potential might offer a useful strategy for nutrient application. The present study was conducted in the Molligipalem village of Karimnagar district, Northern Telangana zone during 2020 to delineate management zones in maize for N, P and K. One hundred of surfaces georeferenced soil samples were collected and analyzed for pH, EC, SOC, available N, P, K, Fe, Mn, Zn and Cu. Soil properties variations were discussed with descriptive statistics and delineation of management zones was done with maximum curvature method. The descriptive statistics revealed that soil is neutral to slightly alkaline in reaction, with the lowest variability. The SOC content and available N was low in soil having less than 20 % variation. Available P and K was medium to high in soil with 20-30 % variation. The available micronutrient status (Fe, Mn, Zn and Cu) in the soil was sufficient with 58 to 75 % variation. Maximum curvature method was found to show wide variation in soil properties and the unit used for distance in m2. In present study, the size of homogeneous zone for pH, EC, SOC, available N, P2O5, K2O, Fe, Mn, Zn and Cu were 3200 m2, 1600 m2, 2400 m2, 1600 m2,1600 m2,2000 m2, 3200 m2, 2400 m2, 4800 m2 and 3600 m2 respectively. As micronutrient content was sufficient in the soil, hence it is not considered delineation of soil management zone. For site specific nutrient management, three soil management zone was estimated using N, P, and K data.